2017
DOI: 10.1111/ecog.03067
|View full text |Cite
|
Sign up to set email alerts
|

Mountain metacommunities: climate and spatial connectivity shape ant diversity in a complex landscape

Abstract: Understanding what drives biodiversity patterns across scales is a central goal of ecology. Both environmental gradients and spatial landscape structure have been found to be important factors influencing species distributions and community composition, and partly reflect the balance of underlying deterministic and stochastic community processes. In some systems, environmental gradients and spatial connectivity are intertwined in that steep environmental gradients serve as boundaries on species movements and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 71 publications
12
60
0
Order By: Relevance
“…A3; σ 2 among /σ 2 total : ω = 0.17; TempBreadth = 0.16). Analyses of ants along elevational gradients in Costa Rica, the United States, Austria, and the Himalayas have documented high elevation phylogenetic clustering (Machac et al 2011, Smith et al 2014, Liu et al 2018, consistent with the similarity in thermal preferences we detected among congeners. As richness patterns are direct products of species' elevational ranges, the distribution of thermal preferences has a large impact; our results suggest a strong effect of the evolutionary temperature preferences of a taxon -here at temperatures in the lower third of the gradient -diffused through some combination of selection and drift as species have diverged, on current richness patterns.…”
Section: Discussionsupporting
confidence: 84%
“…A3; σ 2 among /σ 2 total : ω = 0.17; TempBreadth = 0.16). Analyses of ants along elevational gradients in Costa Rica, the United States, Austria, and the Himalayas have documented high elevation phylogenetic clustering (Machac et al 2011, Smith et al 2014, Liu et al 2018, consistent with the similarity in thermal preferences we detected among congeners. As richness patterns are direct products of species' elevational ranges, the distribution of thermal preferences has a large impact; our results suggest a strong effect of the evolutionary temperature preferences of a taxon -here at temperatures in the lower third of the gradient -diffused through some combination of selection and drift as species have diverged, on current richness patterns.…”
Section: Discussionsupporting
confidence: 84%
“…Elevational gradients are of interest because they are replicated across space and have pronounced environmental changes over short distances (Rahbek 1995, Graham et al 2014. Ants on elevational gradients have been the subject of numerous studies (e.g., Olson 1994, Fisher 1996, 1998, 1999a, Sanders 2002, Sanders et al 2007, Malsch et al 2008, Longino and Colwell 2011, Machac et al 2011, Longino et al 2014, Smith et al 2014, Szewczyk and McCain 2016, Liu et al 2018, Longino and Branstetter 2019, revealing a variety of patterns and suggested causes. Among the insects, ants are a prominent group because of their ubiquity and high biomass (H€ olldobler and Wilson 1990, Wilson andH€ olldobler 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Liu et al (2016) found reduced functional diversity associated with sharp decline in species richness in rubber plantations in southern China. These findings suggest that ant communities do not show phylogenetic responses to habitat differences at small spatial scales, although phylogenetic differences dominate community patterns across broad climatic gradients (Smith et al, 2014;Liu et al, 2017). While the lower species richness in littoral forests was a natural pattern, likely mediated by the abiotic environment, it was anthropogenic pressures that led to habitat loss and alteration of ant communities in both the studies mentioned above.…”
Section: Discussionmentioning
confidence: 87%
“…Machac et al, 2011;Arnan et al, 2014Arnan et al, , 2015Arnan et al, , 2017Smith et al, 2014;Werenkraut et al, 2015;Liu et al, 2017). Machac et al, 2011;Arnan et al, 2014Arnan et al, , 2015Arnan et al, , 2017Smith et al, 2014;Werenkraut et al, 2015;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%